Real-time CO2 production monitoring in stored oats as an indicator of type A trichothecenes and ochratoxin A contamination under simulated environmental conditions - Oluwakayode, Abimbola; Sulyok, Michael; Berthiller, Franz; Verheecke-Vaessen, Carol; Krska, Rudolf; Medina, Angel (MDPI, 2025)
Grain industries are interested in an integrated approach to in-silo grain quality and safety management using carbon dioxide (CO2) measurement with temperature and moisture monitoring. Our study investigates if CO2 production could predict mycotoxin production (T-2 toxin, HT-2 toxin, its glucoside, and ochratoxin A (OTA)) and identify storage conditions exceeding legislative limits in stored oats for the first time. The influence of water activity (aw) levels (0.70–0.95 aw), temperature (15 and 20 °C), and storage duration on (a) Fusarium populations, (b) CO2 respiration rates (RRs), and (c) mycotoxin concentrations in stored oats was examined. One hundred and twenty samples were analysed for multiple mycotoxins by LC-MS/MS. Substantial differences were found in the RRs of oats at ≥0.90 aw at both temperatures. A moderate positive correlation between CO2 and mycotoxins was noticed and mycotoxins exceeded their limits at ≥0.90 aw (22% moisture content) when RR ≥ 25 µg CO2 kg−1 h−1. This knowledge forms the basis for developing decision support systems for improving oats’ storage management.
Keywords: 3214 Pharmacology and pharmaceutical sciences; Fusarium langsethiae; T-2/HT-2 toxin; ochratoxin A; carbon dioxide respiration rate; water activity; LC-MS/MS